Knowledge Retention and Personnel Mobility: The Nondisruptive Effects of Inflows of Experience - Madsen, Tammy L.; Mosakowski, Elaine; Zaheer, Srilata (Organization Science, 2003)
Firms often bring in personnel from rivals to gain tacit knowledge and skills. Personnel new to a firm may broaden the firm's knowledge stock, but may not disrupt the firm's ways of organizing. Instead, personnel inflows may contribute to the retention of a firm's traditional ways of organizing. This study tracks the flow of personnel within and across organizational boundaries (intrafirm and interfirm flows) and geographic boundaries (local and cross-border flows) for multiunit banks operating in the Foreign Exchange Trade Industry from 1973–1993. We test how a firm's retention activity responds to inflows of personnel from different sources (e.g., intrafirm, interfirm, local, and cross-border). The findings show that inflows of personnel from different sources increase a firm's retention activity. Rather than adopting changes in behavior in response to an influx of personnel from within or across spatial boundaries, firms in the foreign exchange industry tend to retain their existing ways of organizing. Personnel inflows from a combination of sources, such as local intrafirm, cross-border intrafirm, local interfirm, and cross-border interfirm, also positively affect retention. By examining the differences in the magnitudes of these effects, we empirically show that considering different sources of personnel inflows in combination is worthwhile.